Bringing Students' Arguments to Life: Testing the Effectiveness of Local Context-based E-Modules through a Project-Based Learning Approach - Ananda, Febby Ayu; Nurhayati, Nurhayati; Purnomo, Mulyadi Eko; Ernalida, Ernalida (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to test the effectiveness of e-modules for writing argumentative essays based on local contexts that are integrated with Project-Based Learning (PjBL). The method used was a quasi-experiment with a non-equivalent control group design. The research sample included class XI.6 as the experimental class and class XI.7 as the control class. The experimental group learned using e-modules at each stage of PjBL, while the control group obtained conventional learning. The results showed that the learning outcomes of the experimental group were significantly higher. Thus, so that e-module-based learning with local context and PjBL is declared effective for argumentative essay writing skills.